Comparison of spontaneous background genomic aberration frequencies among cattle, pig and humans using dual-colored FISH - Rezácová, Olga; Kubícková, Svatava; Cernohorská, Halina; Rubes, Jirí (Chromosome research, 2003)
Spontaneous frequencies of stable chromosomal aberrations in farm animals have not been established yet. The aim of this study was to determine the spontaneous background frequencies of structural chromosomal aberrations in cattle and pig, and to compare them with the established findings in humans. Analysis was carried out on peripheral blood samples taken from 29 cows, 15 calves, 15 boars, 13 piglets, and 23 adult and 12 newborn humans. Dual-colored FISH using whole chromosome painting probes specific for human chromosomes 1 and 4, bovine chromosomes 1 and 7, and pig chromosomes 1 and 13 was performed. Chromosome aberrations were classified according to the PAINT nomenclature. The proportions of aberrant cells and the genomic frequencies of translocations, insertions and dicentrics were measured. The highest background translocation frequency was observed in humans (1.40 +/- 0.92). Data obtained in boars were similar to those obtained in humans. Cows showed much lower values of studied parameters than was expected. There was no statistical difference in any category of aberration frequencies between cows and calves. Significant differences in genomic frequencies of both total and reciprocal translocations were found when comparing boars with piglets and adult humans with newborn babies. Very low levels of spontaneous background translocation frequencies were seen among calves, piglets and newborn human babies.
Keywords: Cattle; Animals; skot; DNA sondy; malování chromozomů; lidé; Translocation, Genetic; Chromosome Painting; genom; prasata; Genome; Metaphase; metafáze; chromozomální aberace; Swine; hybridizace in situ fluorescenční; zvířata; translokace genetická; DNA Probes; In Situ Hybridization, Fluorescence; Chromosome Aberrations; Humans